2004
DOI: 10.1111/j.1600-0501.2004.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of Osseotite® and machined titanium implants in autogenous bone graft. A histologic and histomorphometric study in dogs

Abstract: It has been shown that a roughened implant surface results in a higher percentage of bone to implant contact (%BIC) than a machined one. A modified implant surface using a dual thermo-acid etching process (Osseotite) has been introduced and evaluated clinically, mechanically and histologically. The aim of the present study was the histological evaluation of the %BIC between the Osseotite or machined surfaces and the autogenous bone graft. Twenty-two custom-made split-type 10-mm-long implants having two opposin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
3
23
1
4
Order By: Relevance
“…7). This value represents the maximum area of mineralization observed in vitro on various peptide-IPN surfaces, and is similar to the maximum reported BIC for model studies with titanium implants 55 and mesenchymal stem cells injected in the peri-implant region at the time of implantation. 56 This value may represent a maximum for BIC in vivo.…”
Section: Bone-implant Contact (2 Weeks)supporting
confidence: 55%
“…7). This value represents the maximum area of mineralization observed in vitro on various peptide-IPN surfaces, and is similar to the maximum reported BIC for model studies with titanium implants 55 and mesenchymal stem cells injected in the peri-implant region at the time of implantation. 56 This value may represent a maximum for BIC in vivo.…”
Section: Bone-implant Contact (2 Weeks)supporting
confidence: 55%
“…VEIS et al 26 reported that the BIC value was 32% for acidetched implants versus 17% for machine-turned implants 5 months after implant placement in the mandible of the dog. WENG et al 27 referred to 62%BIC for acid-etched versus 39%BIC for machineturned implants after 4 months in foxhounds.…”
Section: Discussionmentioning
confidence: 98%
“…For example, mesh designed titanium implants were shown to promote soft tissue ingrowth in vivo associated with an enhanced ingrowth of blood vessels 30. Perhaps, a different configuration of surface modification is required for soft tissue adherence compared with surface roughness that is able to support bony integration 31. Kim et al28 reported that parallel microgrooved surfaces implanted in rats exhibited greater connective tissue attachment and thinner fibrous capsules than polished surfaces.…”
Section: Discussionmentioning
confidence: 99%